Early and Late Onset of Voluntary Exercise Have Differential Effects on the Metabolic Syndrome in an Obese Mouse Model - Wagener, A.; Schmitt, A. O.; Brockmann, G. A. (Experimental and Clinical Endocrinology & Diabetes, 2012)
In a mouse model for juvenile obesity, we investigated how the age of onset of voluntary exercise affects factors of the metabolic syndrome. One exercise group had access to running wheels from 3 weeks (representing childhood) and another one from 9 weeks on (early adulthood). Both groups were compared to mice without exercise. The investigations were performed under 2 diets (standard maintenance and high-fat diet). Average daily running activity was independent of diet and exercise. On both diets, mice with exercise from 3 weeks on gained 10 g body weight and 5 g fat mass less than mice without exercise. The highest body weight difference between mice on HFD without exercise and mice on standard maintenance diet with exercise was 24 g. Despite the higher energy expenditure during exercise, young mice did not increase their energy intake adjusted for lean mass, while mice with exercise from 9 weeks had an increased energy intake of 6 kJ per day and therefore could not reduce fat mass on both diets. However, mice with exercise from 9 weeks had better glucose tolerance at 20 weeks than mice with exercise from childhood on. Independently of the age of exercise onset, triglycerides were reduced from 2.4 to 1.7 mmol/l on both diets and insulin levels from 1.5 to 0.3 and 4.5 to 1.8 µg/ml on standard maintenance and high-fat diet, respectively, which represents a considerable improvement. Physical activity seems to have long-lasting effects on body composition and health, but they are different depending on when exercise has begun.
Keywords: adiposity; glucose homeostasis; insulin resistance; prevention; running wheel